Exposure‐response relationships for the efficacy and safety of filgotinib and its metabolite GS‐829845 in subjects with rheumatoid arthritis based on phase 2 and phase 3 studies - Meng, Amy; Anderson, Kacey; Nelson, Cara; Ni, Liyun; Chuang, Shu‐Min; Bellanti, Francesco; Chang, Peter; Comisar, Craig; Kearney, Brian P.; Bartok, Beatrix; Mathias, Anita (British journal of clinical pharmacology, 2022)
Aims Filgotinib is a potent, oral, JAK1‐preferential inhibitor for the treatment of rheumatoid arthritis (RA). This report describes exposure‐response (ER) analyses of filgotinib for dose confirmation based on three phase 3 and two phase 2 studies in moderate to severe RA patients. Methods The pharmacokinetic exposures used in ER analyses were derived from population pharmacokinetic analysis. The exposure‐efficacy relationships were assessed for efficacy endpoints (ACR20/50/70 and DAS28) over effective area under curve (AUCeff), the combined exposures of filgotinib and GS‐829845 (major, active metabolite), with nonlinear logistic regression models developed. Also, a t‐test was performed to compare the exposure between subjects who achieved response and those who did not. For the ER analyses of safety, exposures were examined between subjects who experienced and who did not experience the evaluated safety events, which was conducted separately for filgotinib and GS‐829845. Results The nonlinear logistic regression showed increasing response with increasing exposure, with exposures at 200 mg dose primarily residing on the curve plateau. Also, AUCeff was significantly higher in the subjects who achieved responses compared to those who did not (10 900 vs 9900 h*ng/mL for ACR20, P value < .0001). For exposure‐safety analyses, filgotinib and GS‐829845 exposures were similar irrespective of the presence/absence of the evaluated safety endpoints, indicating no exposure‐safety relationship for common treatment‐emergent adverse events (TEAEs)/laboratory abnormalities and serious TEAEs/infections. Conclusions ER analyses confirmed that filgotinib produced more robust therapeutic effects across the exposure range observed at 200 mg once daily compared to lower doses, and collectively with the lack of exposure‐safety relationship, the 200 mg once daily dose was supported for commercialization.